Die aard en stand van die tradisionele, nie-westerse of stammedisyne in suid-afrika - H.C.J Van Rensburg (AOSIS, 1981)
There exists a long-established system of traditional medicine among Blacks in South Africa next to Westernised health services. The exact extent to which traditional medicine is practised cannot be established, but evidence exists The continued use of the traditthioant ailt hise aslteilrls ,u osefdte nw itdoegleyt.her with Western medicine, is rooted in the traditionally held concepts of health and disease. Illness and death are usually attributed to mystical causes which must be identified and removed by the witchdoctor. Witchdoctors can be divided into distinct categories according to their functions and methods - i.e. diviners and medicine-men or herbalists. The methods used by the witchdoctor are not compatible with Western medicine, but their approach to patients and the community has certain attributes not found in modern medical practice. It is not envisaged that the witchdoctor will cease to play a role in the foreseeable future.